The Influence of Workload and Job Skills on Employee Job Satisfaction with Compensation as An Intervening Variable at The Medan Religious Training Center - Harahap, Tiajijah; Farida Ferine, Kiki (International Journal of Social Science, Education, Communication and Economics (SINOMICS JOURNAL), 2023)
Human resources play a very important role in determining the progress of a country. Even though the country has abundant natural resources, if it is not supported or supported by quality human resources, the country will not be able to progress. The type of research used was associative quantitative research, this research was conducted at the Medan Religious Education and Training Center office, the research population was 72 employees and the sample technique used was saturated sample technique because it counted all populations as samples, data collection used was distributing questionnaires, the research model this is a paht analysis with a measuring tool using smart PLS version 3.3.3. The results of this study are as follows: Workload has a significant negative effect on job satisfaction. Workload has a positive and significant effect on Compensation. Work Skills have a positive and significant effect on Job Satisfaction. Work Skills has a positive and significant effect on Compensation. Compensation has a positive and significant effect on job satisfaction. Workload has a positive and significant effect on Job Satisfaction through Compensation. Work Skills have a positive and significant effect on Job Satisfaction through Compensation.